Tostão contra o milhão: a trajetória política de Jânio Quadros pelo jornal O Estado de São Paulo (1947/1955) - Fidelis, Thiago [UNESP] (2013)
This work has as objective understand the political organization of São Paulo during the democratic period between the Estado Novo and the Revolução de 64, emphasizing the ways which the politic of São Paulo Jânio Quadros used to maintain its image throughout his political career during the study period, as well as their political choices and their modes of administration. Allied to this aspect and understanding the press as a vehicle what publishing something to strive to form opinions about various subjects, the objective of this work is confront the political analysis with the speech of the journal O Estado de São Paulo, the greater periodical of the São Paulo what has journalists and professionals involved with politics, searching interaction with the readers and the rest of society